Recovery study of dangerous drugs in soft drinks using liquid-liquid extraction followed by gas chromatography-flame ionisation detector (GC-FID) - Khai, Lee (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Raves and night clubs are always associated with the recreational drugs, which are also referred as 'club drugs'. Dissolving illegal drugs, such as ketamine and 3,4-methylenedioxymethamphetamine (MDMA), into liquid forms to be disguised as bottled soft drinks is one of the current drug concealment methods. Hence, a recovery study to develop suitable method for detection and quantification of the amount of specific drugs contained in the soft drinks is proposed. The objective of this study is to study the recovery efficiency of liquid-liquid extraction (LLE) method used to extract drugs from the soft drinks. LLE with chloroform allowed the extraction of ketamine and MDMA from the sample soft drinks. Gas Chromatography-Mass Spectrometry (GC-MS) analysis was used to confirm the presence of desired drugs in the extracts, followed by Gas Chromatography-Flame Ionisation Detector (GC-FID) analysis to quantify the amount of desired drugs extracted from the soft drinks. In GC-MS analysis, it was found that the quality of mass spectral match for MOMA (78%- 87%) was lower compared to ketamine (98%) and internal standard (91 %). In recovery study of repeated extraction on same sample, it was found that the amount of drugs recovered were consistent for blackcurrant juice (RSD = 6.77%) and ice lemon tea (RSD = 5.38%), but inconsistent for green tea (RSD = 15.52%) and orange juice (RSD = 29.43%). In recovery study using spiked samples, the average recovery percentage of ketamine from blackcurrant juice was 87.27 ± 5.72 %. The regression curve for recovery ofketamine was found to be sufficiently linear (R2 = 0.997), which indicated that the method was accurate. In brief, the analytical procedures of LLE, coupled with GC-MS and GC-FID in recovery study were found reliable for the extraction, detection and quantitation of ketamine and MDMA in the drug-laced soft drinks.